PENGEMBANGAN INSTRUMEN PENILAIAN SIKAP DISIPLIN SISWA KELAS V SEKOLAH DASAR - Sholihah, Ana Putri; Herpratiwi; Undang Rosidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to produce a proper, practical and effective disciplinary attitude assessment instrument for measuring the disciplinary attitude of fifth grade elementary school students. This research is a type of Research and Development (R&D) research, development is carried out referring to Borg & Gall's theory. The population in this study were educators and students of class V SDN 5 Jatimulyo. The data collection tool uses a valid and reliable questionnaire instrument. The final average results from the validation of evaluation experts and language experts obtained a score of 94% with very valid criteria. The students' practitioner test results were 93% with very practical criteria. The data analysis technique uses the calculation of the percentage of effectiveness of the questionnaire to determine the correctness of the results of the observation score for students' discipline attitudes, which was obtained at 87.70%, the self-assessment discipline attitude score was obtained at 87.99% and the peer-assessment discipline attitude score was obtained at 88.20%. Meanwhile, in assessing the effectiveness of educators' disciplinary attitudes, an average score of 90 was obtained in the very effective category. Based on the results of this research, it can be concluded that the disciplinary attitude assessment instrument is effective for use in elementary schools.